(untitled) (London Journal of Research In Management & Business, 2025)
This study systematically evaluates the effects of managerial overconfidence on corporate capital holdings. According to the theoretical framework, this study conducted an empirical analysis using data on listed Chinese companies from 2010 to 2022. Traditional economic theories are based on rational human assumptions, and theories that explain corporate cash holdings concentrate on the potential uses of corporate cash assets; however, they neglect to consider decision-makers beliefs that ultimately dictate cash utilization and cannot verify the difference between managers overconfidence and over-optimism. Therefore, this study not only verify the difference between managers overconfidence and over-optimism, but also based on psychology theory to explain why cognitive bias leads managers to be more overconfident in China and affects corporate cash holding levels. These findings indicate that managers overconfidence positively associated with corporate cash holdings. Additionally, the high-quality internal controls mitigate overconfident managers holding more cash by alleviating information asymmetry. Collectively, this study effectively connects cognitive psychology to enrich the research on the correlation between managerial overconfidence and cash holdings. In addition, these findings illustrate the important implications of enforcing cash-use efficiency and alleviating cognitive bias in overconfident managers.